Six months of exclusive breast feeding: how good is the evidence?. (13th January 2011) - Fewtrell, Mary; Wilson, David C; Booth, Ian; Lucas, Alan
Abstract : The recommendation that UK mothers should exclusively breast feed for six months is a controversial area in infant nutrition. Mary Fewtrell and colleagues review the evidence and ask if the time is right for reappraisal of this advice